Dementia, personhood and embodiment: What can we learn from the medieval history of memory?. (May 2013) - Katz, Stephen
Memory and dementia are historical ideas that preceded the development of modern neuroscientific, psychogeriatric and medical approaches to aging and cognitive impairment. This article explores the value of such historical ideas in order to understand the discourses and metaphors by which Western thought has individualized memory as the guarantor of rational personhood, while at the same, treating memory decline as a threat to healthy and successful aging. Discussion focuses on the relationship between memory and the body in the classical and medieval ars memoria (the art of memory) and in the early modern philosophies of personhood, particularly the work of John Locke. Conclusions consider the significance of Western culture's history of embodied memory as it moved from cosmic to individual to neurocognitive sites for our wider views about the treatment of dementia.